Hot deformation behavior, dynamic recrystallization and precipitation behavior of a novel Er, Zr-microalloyed Al–Cu–Mg alloy - Zhizheng Rong; Xiaolan Wu; Fangyan He; Shengping Wen; Xiangyuan Xiong; Kunyuan Gao; Wu Wei; Hui Huang; Zuoren Nie (Journal of Materials Research and Technology)
The intrinsic relationship between hot deformation behavior and microstructure evolution in Er, Zr-microalloyed Al–Cu–Mg alloy was investigated by isothermal hot compression test. The constitutive model and thermal process map were established, the effects of the Zener-Hollomon parameter (Z) on dynamic recrystallization and precipitation behavior was determined. The results showed that the predicted value of the strain-compensated Arrhenius constitutive model fit well with the friction corrected data after the strain fitting. As the lnZ value increased, the deformed alloy exhibited higher dislocation density, smaller average grain size and was more conducive to the existence of large-sized precipitates (mainly Al–Cu phase, Al–Mg–Si phase, Mn–Si-rich phase). The L12 ordered Al3(Er, Zr) particles (∼20 nm) formed by the co-addition of Er and Zr. During hot deformation, Al3(Er, Zr) particles and Mn–Si-rich phase demonstrated exceptional thermal stability and coarsening resistance, which effectively refined the grain size of the alloy and broadened its optimal hot-working window (0.1–0.01s −1, 450–500 °C).